PEMBERIAN PENYULUHAN DAN DEMONSTRASI PERAWATAN LUKA DIABETES MELITUS - Nuridayanti, Anik (Jurnal LENTERA, 2024)
One of the potential causes of the increasing prevalence of diabetes mellitus isinjury occurs. Uncontrolled wounds will become worse and hinder the healing process. The aim of providing counseling and demonstrations on diabetes mellitus wound care to families and Diabetes Mellitus sufferers is to increase knowledge and skills that can help families and Diabetes Mellitus sufferers to care for diabetes mellitus wounds and speed up the wound healing process. Method of providing wound care at the Scania care center with counseling and demonstration. Results Providing counseling and demonstrations on wound care for diabetes mellitus patients, patients and their families can care for wounds and speed up the healing process. Conclusion: Providing counseling and demonstrating correct wound care for Diabetes Mellitus patients can increase the knowledge and skills of families and patients in caring for wounds of Diabetes Mellitus patients.   Kata Kunci: Perawatan Luka, Pasien Diabetes Melitus